Advanced molecular dynamics and chemical kinetics - Billing, Gert D. (John Wiley & Sons, 1997)
A comprehensive, in-depth presentation of theoretical underpinnings and mathematical techniques This is the first book of its kind to combine all the theories of molecular reaction dynamics and chemical kinetics in a single source. It provides a sophisticated treatment of the material that functions both as a professional reference and a high-level text for PhD and postdoctoral researchers. Advanced Molecular Dynamics and Chemical Kinetics offers exceptional, in-depth coverage and includes a complete discussion of the theoretical as well as mathematical presentation of techniques. It features relevant exercises as well as comprehensive coverage of: Second Quantization Semiclassical Theory Quantum Theory of Reaction Rates Feynman Path Integrals Wavepacket Propagation and Grid Methods Photodissociation Molecular Properties of Solvated Molecules Quantum Model for Electron Transfer Electron Transfer Coupling Elements Proton Transfer Reactions in Solution This is the ideal reference for seasoned professionals in molecular reaction dynamics as well as for younger researchers who may want to enter the field or simply wish to learn more about it.